Water-induced structural changes in poly(lactic acid) and PLLA-clay nanocomposites. (19th December 2016) - Beltrán, F.R.; de la Orden, M.U.; Lorenzo, V.; Pérez, E.; Cerrada, M.L.; Martínez Urreaga, J.
Abstract: The influence of nanoclays on the structural changes of hydrated poly( l -lactic acid) (PLLA) was investigated at two temperatures, above and below its Tg. Samples of a commercial PLLA and nanocomposites with 2 wt% of an organically modified montmorillonite and an unmodified halloysite were kept in a phosphate buffered solution for different times at 37 and 58 °C and then characterized. The crystallinity degrees and the nature of the crystalline structures developed were determined by differential scanning calorimetry, X-Ray Diffraction and Fourier Transform infrared spectroscopy. While in the cold crystallization of PLLA in dry conditions the α form is obtained only above 100 °C, different mixtures of α and α′ forms were obtained in water at 58 °C, depending on the clay used. The hydrolytic degradation of PLLA played a main role in the structural transformations found at long immersion times, since the short chains formed allowed greater crystallinity degrees and leaded to more perfect crystals. PLLA structure is changed by clays because of its ability as nucleating agents but also due to its effect on the hydrolytic degradation. The unmodified tubular halloysite inhibited degradation, so that lower degrees of crystallinity were obtained in the halloysite based nanocomposite. On the other hand, the modified montmorillonite acted as catalyst of degradation, which explained the appearance of crystalline structures in the nanocomposite with montmorillonite after 84 days of immersion at 37 °C. Graphical abstract: Highlights: Mixtures of α and α′ polymorphs are developed in hydrated PLLA at 58 °C. Hydrolysis plays a main role in the PLLA crystallization at long immersion times. The crystallization of hydrated PLLA depends on the chemical nature of the clay. Montmorillonite induces the crystallization of hydrated PLLA even at 37 °C.